ANALISIS SARANA DAN PRASARANA PENDIDIKAN DI SMA SANTUN UNTAN PONTIANAK - Teodardus, Teodardus; Aminuyati, Aminuyati; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this research is "Analysis of Education Facilities and Infrastructures  Senior High Schools in santun untanPontianak". General problem of this thesis is "to describe educational facilities and infrastructure. The sub-problem is how is the availability of educational facilities and infrastructure, how is the feasibility of educational facilities and infrastructure in Senior High Schools  santun untan Pontianak. The data collection tool used in this paper is interview guidelines, observation sheets and triangulation. The analysis this thesis is presented in a descriptive qualitative manner by using informants from the principal of 1 person, the manager of a computer laboratory 1 person and the manager of a library of 1 person. The results of this study indicate that in the fulfillment of education facilities and infrastructure there are 17 infrastructure that are already available but the provision of facilities in them is still lacking so that there are 6 infrastructure that are not feasible to use and 11 infrastructure that is suitable to be used. from the results of interviews with principals, managers of computer laboratories and library managers which became obstacles in the provision of educational facilities and infrastructure due to lack of funds. Keyword: educational facilities and infrastructure